2012
DOI: 10.1002/uog.10102
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic fetal head position to predict mode of delivery: a systematic review and bivariate meta‐analysis

Abstract: 0.39 (95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
0
29
1
1
Order By: Relevance
“…Furthermore, a number of studies have demonstrated the superiority of ultrasound over digital examination for this aim, and are consistent and unequivocal in their support of its use as the gold standard for this clinically important variable 1 -3 . Sonographic assessment of fetal head position can offer extremely valuable information in certain clinical situations, for instance before instrumental delivery, whereas it seems to be a poor predictor of mode of delivery 3,4 .…”
Section: Letters To the Editor Ultrasound In Labor: A Caregiver's Permentioning
confidence: 99%
“…Furthermore, a number of studies have demonstrated the superiority of ultrasound over digital examination for this aim, and are consistent and unequivocal in their support of its use as the gold standard for this clinically important variable 1 -3 . Sonographic assessment of fetal head position can offer extremely valuable information in certain clinical situations, for instance before instrumental delivery, whereas it seems to be a poor predictor of mode of delivery 3,4 .…”
Section: Letters To the Editor Ultrasound In Labor: A Caregiver's Permentioning
confidence: 99%
“…Certes, l'échographie permet d'améliorer le diagnostic de variété postérieure, cependant son utilité clinique n'a à l'heure actuelle pas été démontrée pour améliorer la prise en charge des femmes ou diminuer le risque de complication. En effet une métaanalyse publiée en 2012, regroupant les données de 11 essais randomisés incluant 5053 femmes, retrouvait que la réalisation d'une échographie en cours de travail pour vérifier la présentation foetale ne permettait pas de diminuer le risque de césarienne [26]. En France, un essai randomisé, non encore publié a été réalisé comparant toucher vaginal seul versus contrôle systématique de la variété pendant le travail par l'échographie et ne retrouvait aucun bénéfice à contrôler systématiquement la présentation foetale.…”
Section: Place De L'échographie Pour Le Diagnostic Des Variétés Postéunclassified
“…In the systematic review published in this issue of the Journal, the authors attempt to determine whether sonographic assessment of fetal head position (or, in their words, ‘assessment of occipital position’) at the onset of spontaneous labor or induction may predict the mode of delivery (vaginal vs Cesarean) in a large group of patients51. This objective is altruistic in that Cesarean delivery, if deemed necessary (and performed) relatively early, may circumvent or at least mitigate maternal morbidities associated with Cesarean delivery performed later in labor, following arrest of labor or failed attempt at vaginal birth52, 53.…”
Section: Can Sonographic Depiction Of Fetal Head Position Prior To Ormentioning
confidence: 99%